Method and system for determining formula of high-ductility composite material based on lake and reservoir deposits, product and preparation method of high-ductility composite material

By obtaining and optimizing the particle distribution characteristics of lake and reservoir silt, and combining modified carbon fibers, a high-ductile composite material suitable for the repair of large-deformed parts of water conservancy and hydropower projects and the Yangtze River protection pipeline network is prepared, which solves the problem of the extremely fine particles of lake and reservoir silt being difficult to resource utilization, and realizes the resource utilization of full-level distribution and coordinated disposal of multiple solid waste.

CN119647120AActive Publication Date: 2025-03-18CHANGJIANG RIVER SCI RES INST CHANGJIANG WATER RESOURCES COMMISSION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411760145.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-18
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The extremely fine particles of lake and reservoir silt are difficult to utilize in resource utilization, and the existing technology has limited scope of application in lake and reservoir silt practice, so it is impossible to fully utilize the fully equipped silt.

Method used

By obtaining the particle distribution characteristics of Huku sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano SiO2, cement and ultrafine powder sand in Huku, the optimized formula of the mixed powder is determined, and combined with modified carbon fiber, the water effluent pumped composite materials and jet repair composite materials are prepared to realize the coordinated disposal of multiple solid waste and high-value utilization.

Benefits of technology

The full-grade resource utilization of lake and reservoir silt is realized. The prepared high-ductility composite materials have good deformation performance and crack resistance. They are suitable for special parts such as large-deformed parts of water conservancy and hydropower projects and repair of large-scale protection pipelines in the Yangtze River.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119647120A_ABST
    Figure CN119647120A_ABST
Patent Text Reader

Abstract

The invention discloses a method and a system for determining a formula of a high-ductility composite material based on lake and reservoir deposits, a product and a preparation method of the product, and belongs to the technical fields of water conservancy and hydropower, transportation and construction and building materials. The determination system comprises an acquisition module for acquiring particle distribution characteristics of a lake and reservoir sludge-red mud-steel slag modified mixture, blast furnace mineral powder, nano SiO2, cement and lake and reservoir superfine silt; the first determination module is used for determining a formula optimization model of the mixed powder according to the obtained particle distribution characteristics of the lake and reservoir sludge-red mud-steel slag modified mixture, the blast furnace mineral powder, the nano SiO2, the cement and the lake and reservoir superfine silt; the formula optimization model of the mixed powder comprises a first objective function and a first constraint condition; and the second determination module is used for determining the formula of the high-ductility composite material according to the formula optimization model of the mixed powder and the basic model of the auxiliary agent. The system is adopted to determine an optimal formula, the hydraulic high-ductility composite material based on the lake and reservoir deposits is prepared, the lake and reservoir deposits are utilized, and the prepared composite material is good in deformation performance and high in crack resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical fields of water conservancy and hydropower, transportation, and construction materials, and in particular relates to a method for determining a formula of a high-ductility composite material based on lake sediments, a system and a product, and a preparation method thereof. Background Art

[0002] Affected by soil erosion and human activities, reservoirs have been seriously silted up and lakes have shrunk. The functionality, safety and comprehensive benefits of reservoirs and lakes have declined, which has become one of the bottlenecks restricting my country's economic and social development.

[0003] There are about 98,000 reservoirs in my country with a total storage capacity of 930.6 billion cubic meters. Affected by soil erosion and human activities, reservoirs generally have different degrees of siltation and storage capacity shrinkage, with an average annual storage capacity siltation rate of about 2%. In particular, due to the lack of sand flushing conditions, small and medium-sized reservoirs have become more seriously silted after years of operation. Soil erosion and human activities such as wastewater and waste discharge have also caused problems such as the fragmentation of river and lake systems, siltation blockage, and poor connectivity, which have had a serious impact on the integrity of river and lake systems and ecosystems. At present, the treatment and resource utilization technologies for lake and reservoir silt include dehydration treatment technology, building materials method, sludge landfill method, sludge composting method, sludge blending method, chemical consolidation method, anaerobic biogas production method and dry distillation treatment method. Among them, the dehydration of lake and reservoir silt and the utilization of building materials is an effective way to absorb it on a large scale. The silt in lakes and reservoirs is large in scale and has a wide range of particle sizes, including larger stones, sand and extremely fine silt and clay. Usually, after sediment separation, some silt that meets the standards for construction sand and gravel can be used directly, while the content of extremely fine silt and extremely fine clay particles accounts for a large proportion and has a complex composition. Their large-scale, green and efficient disposal has become a key technical bottleneck restricting the safety of water projects and the restoration of river and lake ecosystems.

[0004] In recent years, with the implementation of the pilot project of ecological desilting of lakes and reservoirs, some studies have explored the resource utilization of ultra-fine sediment, including making it into ceramsite, bricks, firing cement and using it as construction soil. For example, the Chinese invention patent with patent number CN115745483A uses polycarbonate and asphalt particles to bind sediment fine particles under the action of 120℃ hot air flow under high-speed air flow spray below 120℃ to obtain modified spherical particles with a particle size of 200-500μm, and then adds cement, silicon powder, latex powder, steel fiber, water and 80-180μm sediment coarse particles to make high-strength binder; this patented technology only uses a part of the ultra-fine particles and coarse particles in the sediment, and the compressive strength of the binder obtained reaches about 100MPa, and does not make full use of the fully graded sediment. The Chinese invention patent with patent number CN115677279A provides a method for the development and preparation of cementation of ultrafine granular sediment in the reservoir area. According to the moisture content, mud content, particle grading and performance analysis of the sediment, the optimal mix ratio of cement + silica powder, cement + silica powder + fly ash + ultrafine powder combination cementitious material system is proposed. The invention first determines the conditions for cementation and draws a distribution map of available granular materials through drilling, stratified sampling and analysis, and then collects and cements the sediments that meet the cementation conditions. However, in the practice of dredging lakes and reservoirs, the scale of sediments is huge. From the perspective of environmental and functional restoration, all sediments are required to be disposed of on shore, rather than selecting appropriate grading in a targeted manner. Therefore, the scope of application of the above-mentioned patent technology has certain limitations.

[0005] Judging from the existing research results, the technology for large-scale and resource-based utilization of ultra-fine particles of lake and reservoir sediments is still immature. By utilizing the characteristics of ultra-fine particles of sediments and co-disposing them with the characteristic solid waste of the basin, and combining water project construction with the needs of basin environmental protection, developing high-toughness composite materials with good deformation adaptability is an innovative idea for the resource utilization of ultra-fine particles of lake and reservoir sediments. It can provide an innovative path for the last mile of ecological dredging of lakes and reservoirs, and can also contribute innovative solutions to the coordinated disposal of multiple solid wastes in the basin. Summary of the invention

[0006] In view of the above technical problems, the present invention proposes a method, system, product and preparation method of a high-ductility composite material formula based on lake sediment. The present invention utilizes the silt and ultrafine silt separated from the sediment of lake sediment with clay content as the main component, combines the solid waste steel slag and red mud in the basin, alkali-heat modifies the silt as a part of the cementitious material, screens the ultrafine silt to obtain ultrafine particles with a particle size of 300 μm and a particle size of less than 150 μm, and adds modified carbon fiber to prepare hydraulic pumping composite materials and jet repair composite materials respectively, so as to achieve the coordinated disposal and high-value utilization of multiple solid wastes. And the hydraulic high-ductility composite material prepared by the present invention based on lake sediment has good deformation performance and strong crack resistance, which not only solves the problem that the ultrafine particles of lake sediment are difficult to be utilized as resources, but also utilizes the waste carbon fiber for reinforcement and toughening. The preparation process has the technical advantages of good processability, simple preparation process and no pollution to the environment, and can be used for special parts such as large deformation parts of water conservancy and hydropower projects or repair of the Yangtze River protection pipeline network.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] One of the technical solutions of the present invention:

[0009] A system for determining the formulation of high-ductility composite materials based on lake sediments, comprising:

[0010] Acquisition module, obtain lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , particle distribution characteristics of cement and ultrafine sand in lakes and reservoirs;

[0011] The first determination module takes the maximum amount of ultrafine sand added to the lake as the target, and is used to obtain the lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 The particle distribution characteristics of cement and ultrafine sand from lakes and reservoirs determine the formula optimization model of mixed powder (composed of five raw materials);

[0012] The mixed powder formula optimization model includes a first objective function and a first constraint condition;

[0013] The second determination module is used to determine the formula of the high-ductility composite material according to the formula optimization model of the mixed powder and the basic model of the auxiliary agent.

[0014] Preferably, the particle distribution characteristics include characteristic particle size and cumulative particle size distribution percentage;

[0015] Among them, lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 The corresponding cumulative particle size distribution percentage is determined by the characteristic particle sizes of cement and ultrafine sand from lakes and reservoirs.

[0016] Preferably, when the maximum particle size of the ultrafine sand does not exceed 150 μm, the composite material obtained according to the formula determined by the system is a repaired ECC (jet repaired high ductility composite material);

[0017] At this time, the first objective function is: D8-12 (0.68 μm), D46-54 (15.25 μm) and D89-91 (102.46 μm);

[0018] in,

[0019] And so on;

[0020]

[0021] Among them, q is the coefficient, D q D is the particle size of a single raw material in the mixed powder; q min is the minimum particle size of the mixed powder; D q max is the maximum particle size of the mixed powder (the same below);

[0022] In the above formula, i is the lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , cement and lake ultrafine sand; x is the mass percentage of any raw material in the mixed powder; D is the particle size of each raw material in the mixed powder; the same below;

[0023] The first constraint condition is:

[0024]

[0025] 40%≤x 超细粉沙 ≤60% wt ;

[0026]

[0027] Preferably, when the maximum particle size of the ultrafine sand does not exceed 300 μm, the composite material obtained according to the formula determined by the system is a hydraulic ECC (hydraulic pumping high ductility composite material);

[0028] The first objective function is D8-12 (0.84 μm), D46-54 (26.57 μm) and D89-91 (201.15 μm);

[0029] The first constraint condition is:

[0030]

[0031] 40%≤x超细粉沙 ≤60% wt ;

[0032]

[0033] Preferably, the auxiliary agent includes a water reducing agent, a swelling agent and modified carbon fiber.

[0034] Preferably, the expansion agent is a type II calcium-magnesium composite expansion agent that meets T / CECS10082-2020.

[0035] Preferably, the modified carbon fiber is a recyclable modified carbon fiber obtained by crushing and high-temperature pyrolysis of discarded aircraft shells to remove resin.

[0036] Preferably, the water reducer comprises a high-performance polycarboxylate water reducer; wherein the water reducer needs to be dissolved in water before use, and the mass ratio of the water reducer to water is 1:1.

[0037] Preferably, the basic model of the auxiliary agent is related to the mass of the mixed powder and the volume of the high ductility composite material;

[0038] The basic model of the adjuvant includes a second objective function and a second constraint;

[0039] Wherein, the second objective function is the mass of the mixed powder and the volume of the high ductility composite material;

[0040] The second constraint is:

[0041] The bulking agent is 2%-4% of the mixed powder mass; and / or

[0042] The water reducing agent is 0.5%-2% of the mixed powder mass; and / or

[0043] The modified carbon fiber is 1%-3% of the total volume of the high ductility composite material.

[0044] The second technical solution of the present invention:

[0045] A method for determining a formula of a high-ductility composite material based on lake sediments, using the above system to perform the following steps:

[0046] (1) Use the acquisition module to obtain lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , particle distribution characteristics of cement and ultrafine sand in lakes and reservoirs;

[0047] (2) According to the principle of closest packing, with the goal of maximizing the amount of ultrafine sand, the first determination module is used to determine the optimal formula of the mixed powder;

[0048] (3) Determine the optimized formula of high ductility composite materials using the second determination module and the basic model of auxiliary agents.

[0049] The third technical solution of the present invention:

[0050] A high-ductility composite material based on lake sediments, which conforms to the optimized formula of the high-ductility composite material determined by the above determination system or determination method, and the high-ductility composite material includes the following raw materials:

[0051] Lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , cement, lake and reservoir ultra-fine sand and auxiliary agents.

[0052] Preferably, the lake sludge-red mud-steel slag modified mixture is prepared by uniformly mixing lake sludge, red mud and steel slag in a mass ratio of (4-6):(1-2):(1-2) and then subjecting to alkali-thermal modification.

[0053] Preferably, the blast furnace ore powder is S95 slag powder, and its specific surface area is not less than 350m 2 / kg.

[0054] Preferably, the nano-SiO 2 It is SF85 grade silicon powder.

[0055] Preferably, the cement is 42.5P·O ordinary Portland cement meeting GB 175-2023.

[0056] Preferably, the lake and reservoir ultrafine sand is ultrafine particles with a maximum particle size of no more than 300 μm or no more than 150 μm obtained by further screening the lake and reservoir sediment after sediment separation, and its apparent bulk density is not less than 2500 kg / m 3 , the bulk density is not less than 1280kg / m 3 .

[0057] The fourth technical solution of the present invention:

[0058] A method for preparing a high-ductility composite material based on lake sediments comprises the following steps:

[0059] 1. Obtaining an optimized formula of a high-ductility composite material according to the above determination system or determination method;

[0060] 2. Weigh each raw material according to the optimized formula for use;

[0061] 3. According to the ultra-fine sand, cement, nano-SiO 2 , lake sludge-red mud-steel slag modified mixture, and blast furnace ore powder are added into a mixer in this order, and stirred for 60 seconds to obtain a mixture;

[0062] 4. Add an auxiliary agent to the mixture and stir it evenly to obtain the high ductility composite material.

[0063] Preferably, the specific operations of step 4 are:

[0064] The expansion agent and the modified carbon fiber are added to the mixture and stirred for 30 seconds, and then a water reducing agent is added and stirred for 60 seconds to obtain the high ductility composite material.

[0065] Preferably, if the prepared high-ductility composite material is a spray-repaired high-ductility composite material, the spray pressure after adding the auxiliary agent is 0.8-1.2 MPa;

[0066] The swelling agent is 2%-4% of the mass of the mixed powder;

[0067] The water reducing agent is 1.0%-1.5% of the mass of the mixed powder;

[0068] The modified carbon fiber accounts for 1% to 3% of the total volume of the high-ductility composite material.

[0069] Preferably, if the prepared high-ductility composite material is a hydraulic pumping high-ductility composite material, the swelling agent is 1%-3% of the mass of the mixed powder;

[0070] The water reducing agent is 0.5%-2% of the mass of the mixed powder;

[0071] The modified carbon fiber is 2%-2.5% of the total volume of the high ductility composite material.

[0072] Compared with the prior art, the present invention has the following advantages and technical effects:

[0073] (1) Full gradation utilization of lake and reservoir sediments

[0074] The ultrafine sand of lake sediment provided by the present invention can account for 40% to 60% of the composite material by weight, and the sludge with high clay content is used as a cementitious material after being combined with red mud and steel slag for alkali-heat modification. 2 Powders such as these are densely stacked to fill the gaps between ultrafine sand particles, achieving high density and high strength while realizing full-gradation resource utilization of silt, thus overcoming the global problem that extremely fine particles in lake and reservoir silt are difficult to utilize as resources.

[0075] (2) Flexible construction methods

[0076] The lake and reservoir silt-based composite material provided by the present invention is designed for two casting methods, namely, jet repair and pumping construction of large deformation parts of hydraulic structures. When designing the composite powder material, the maximum particle size of the ultrafine sand is controlled not to exceed 150μm and 300μm respectively. The high-toughness composite powder is obtained by the design method proposed by the present invention, and the incorporation of modified carbon fiber and water reducer is controlled, so that the construction performance of the mixture can be regulated and adjusted, and it is respectively suitable for jet construction for repair and large-flow pumping construction of hydraulic structure parts, and has strong applicability and broad application prospects.

[0077] (3) Highly green and environmentally safe

[0078] The high-toughness composite material provided by the present invention uses lake sediment as the main raw material. For sludge containing some heavy metals, after coordinated alkali-heat modification with red mud and steel slag, the strong alkali of red mud and the mineral alkali of steel slag can be used to solidify and stabilize the heavy metals, which can fully utilize the resource attributes of the sediment and ensure environmental safety. At the same time, recycled carbon fiber is obtained by processing and modifying the abandoned aircraft shell, which is dispersed in the composite material. Through random distribution, bridge bonds and energy dispersion, the interfacial bonding between carbon fiber and cement-based materials is enhanced, and the strength and toughness of the composite material are improved. The waste recycling and substitution of raw materials such as cementitious materials, micro-aggregates, and admixtures is achieved, and the green level of the composite material is improved.

[0079] (4) Good processing performance and economy

[0080] The lake and reservoir silt provided by the present invention is based on the principle of using local materials. The silt generated by lake and reservoir dredging is directly screened after dehydration, ultrafine sand is directly utilized, and silt is modified and utilized. It is combined with basin solid waste and waste carbon fiber for modification and reuse, thus avoiding large-scale land occupation and stacking of silt. The preparation process of the composite material is similar to that of ordinary cement-based materials, and only the feeding sequence and mixing time need to be adjusted. It has good processing performance and significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0082] Figure 1 This is a process flow chart for preparing a high-ductility composite material based on lake sediments of the present invention;

[0083] Figure 2 This is the XRD pattern of lake sediment;

[0084] Figure 3 is the compressive strength of the composite material prepared in Example 3;

[0085] Figure 4is the flexural strength of the composite material prepared in Example 3. DETAILED DESCRIPTION

[0086] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0087] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0088] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0089] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0090] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0091] like Figure 1 As shown, the present invention discloses a method for preparing a high-toughness composite material based on lake sediment, comprising the following steps:

[0092] S1: Testing lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , particle distribution characteristics of ordinary Portland cement and ultrafine sand from lakes and reservoirs;

[0093] S2: Based on the principle of the most compact packing of powder, with the goal of maximizing the amount of ultrafine sand, restrictive conditions are set for the two pouring methods of jet repair and hydraulic pumping construction:

[0094] ① The cumulative particle size distribution percentage corresponding to the characteristic particle size of the mixed powder should be within the control index range, see Table 1 and Table 2;

[0095] Table 1 Control index of powder characteristic value of ultrafine sand from lake reservoir for jet repair of high ductility composite materials

[0096] index <![CDATA[P 0.68μm ]]> <![CDATA[P 15.25μm ]]> <![CDATA[P 102.46μm ]]> Mica Mud content The tightest value 0.1 0.5 0.9 2 1 Control scope 0.08~0.12 0.46~0.54 0.89~0.91 <2% <2%

[0097] Table 2 Control index of characteristic value of ultra-fine sand from lakes and reservoirs for high ductility composite material powder used in hydraulic pumping

[0098] index <![CDATA[P 0.84μm ]]> <![CDATA[P 26.57μm ]]> <![CDATA[P 201.15μm ]]> Mica Mud content The tightest value 0.1 0.5 0.9 2 1 Control scope 0.08~0.12 0.46~0.54 0.89~0.91 <2% <2%

[0099] ② When used for hydraulic pumping construction to prepare hydraulic high-ductility composite materials, the total mass ratio of the adhesive material should not be less than 40%; when used for spraying construction to prepare high-ductility repair composite materials, the total mass ratio of the adhesive material should not be less than 50%; the adhesive material should contain lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 2. Ordinary Portland cement ultrafine particle powder material is used to fill the gaps between ultrafine sand particles in lakes and reservoirs and produce enough gelling hydration products to form a whole;

[0100] ③ The mass percentage of ultrafine silt in lakes and reservoirs shall not be less than 40% and not more than 60%;

[0101] ④ The raw material composition is in the form of percentage, and the sum of each raw material is normalized to 1.

[0102] The above constraints:

[0103]

[0104] S3: Weigh the powder material according to the mass ratio of each raw material of the mixed powder determined in the above step (1), weigh the calcium-magnesium composite expansion agent according to 2%-4% of the mass of the mixed powder material, weigh the high-performance water reducer and an appropriate amount of water according to 0.5%-2% of the mass of the mixed powder material, dissolve the high-performance water reducer in water for later use (the mass ratio of the water reducer to water is 1:1), and weigh the modified carbon fiber according to 1%-3% of the total volume of the high-ductility composite material.

[0105] S4: According to the ultra-fine sand of lakes and reservoirs, ordinary Portland cement, nano-SiO 2 , lake sludge-red mud-steel slag modified mixture, and blast furnace ore powder are added into the mixer in this order and stirred for 60 seconds. Then, the calcium-magnesium composite expansion agent and modified carbon fiber are added. The mixer is stirred for 30 seconds. Then, the water reducer is added and stirred for 60 seconds. Then, a high ductility composite material is obtained for injection construction or pumping construction.

[0106] In some preferred embodiments, the method for preparing the lake sludge-red mud-steel slag modified mixture in step S1 comprises the following steps:

[0107] The lake sludge, red mud and steel slag are mixed uniformly in a mass ratio of (4-6): (1-2): (1-2); the mixed materials are subjected to medium temperature calcination and alkali thermal modification at a temperature of 200-300° C. The specific steps are as follows:

[0108] According to the mass ratio of (4-6):(1-2):(1-2), lake sludge, red mud and steel slag are weighed and mixed thoroughly;

[0109] Place the mixture in an oven and dry it at 60-100°C to remove excess moisture and ensure that the material is dried evenly;

[0110] Put the dried mixture into a high temperature furnace, set the temperature to 200-300℃, control the calcination time to 2-3 hours, and then cool naturally:

[0111] Add 1.0 mol / L sodium hydroxide to the cooled mixture, with a mass ratio of (mixture: sodium hydroxide) = (10:1), mix thoroughly, heat again to 100-200°C, keep for 1 hour, then cool the alkali-heat-modified material to room temperature and grind it to a specific surface area of ​​not less than 500m 2 / kg of lake sludge-red mud-steel slag modified mixture.

[0112] In some preferred embodiments, the preparation process of the modified carbon fiber in step S3 is:

[0113] The carbon fiber composite materials of discarded aircraft shells are screened, cleaned, cut, crushed and ground to obtain short fiber-shaped carbon fibers and resin powder with a length of 10 to 30 mm;

[0114] The short fiber-like carbon fiber is immersed in a NaOH solution with a concentration of 1.0 mol / L, stirred for 30 minutes, taken out and dried in an oven at 105° C. to obtain the modified carbon fiber.

[0115] In addition, the present invention also discloses a high-toughness composite material based on lake sediments prepared by the above preparation method.

[0116] The high-ductility composite material based on lake sediment provided by the present invention and the preparation method thereof use lake sediment as the main raw material, wherein ultrafine silt with extremely fine particles replaces standard quartz sand as aggregate, and the composite material is designed with the goal of maximizing the amount of ultrafine silt; utilizing the strong alkalinity of red mud, a characteristic solid waste in the Yangtze River Basin, and the characteristics of the mineral alkali of steel slag itself, silt with high clay content is used with red mud and steel slag for alkali-heat modification as a cementitious material, and the lake sediment before and after alkali-heat conversion (XRD spectrum as shown in FIG. Figure 2 As shown), the synergistic alkali-thermal modification and resource utilization of silt, red mud and steel slag in the basin are realized; the present invention also innovatively utilizes the modified carbon fiber obtained by processing and modifying the abandoned aircraft shell, and utilizes the random distribution of carbon fiber in the gelling system and the bridging and energy transfer effects under load, which has a good reinforcement and toughening effect; the high-ductility composite material prepared based on this method not only realizes the full-gradation use of the silt of the lake and reservoir on the shore, but also realizes the synergistic disposal and resource utilization of multiple solid wastes, so that the prepared product has technical advantages such as high strength, high toughness, and crack resistance, and has broad application paths.

[0117] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0118] The raw materials used in the present invention are all purchased from the market.

[0119] The technical solution of the present invention is further illustrated by the following embodiments.

[0120] Example 1

[0121] A system for determining the formulation of high-ductility composite materials based on lake sediments, comprising:

[0122] Acquisition module, obtain lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , cement and lake ultrafine sand particle distribution characteristics (characteristic particle size and cumulative particle size distribution percentage); among them, lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , the characteristic particle sizes of cement and ultrafine sand from lakes and reservoirs determine the corresponding cumulative particle size distribution percentage;

[0123] The first determination module takes the maximum amount of ultrafine sand added to the lake as the target, and is used to obtain the lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 The particle distribution characteristics of cement and ultrafine sand from lakes and reservoirs determine the formula optimization model of mixed powder (composed of five raw materials);

[0124] The mixed powder formula optimization model includes a first objective function and a first constraint condition;

[0125] (i) When the maximum particle size of the ultrafine sand does not exceed 150 μm, the composite material obtained according to the formula determined by the system is a spray-repaired ECC (spray-repaired high ductility composite material);

[0126] At this time, the first objective function is: D8-12 (0.68 μm), D46-54 (15.25 μm) and D89-91 (102.46 μm);

[0127] in,

[0128] And so on;

[0129] In the above formula, i is the lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , cement and lake ultrafine sand; x is the mass percentage of any raw material in the mixed powder; P is D is the particle size of each raw material in the mixed powder; the same below;

[0130] The first constraint is:

[0131]

[0132] 40%≤x 超细粉沙 ≤60% wt ;

[0133]

[0134] (ii) When the maximum particle size of the ultrafine sand does not exceed 300 μm, the composite material obtained according to the formula determined by the system is hydraulic pumping ECC (hydraulic pumping high ductility composite material);

[0135] The first objective function is D8-12 (0.84 μm), D46-54 (26.57 μm), and D89-91 (201.15 μm);

[0136] The first constraint is:

[0137]

[0138] 40%≤x 超细粉沙 ≤60% wt ;

[0139]

[0140] A second determination module is used to determine the formula of the high-ductility composite material according to the formula optimization model of the mixed powder and the basic model of the auxiliary agent (including a water reducer, an expansion agent and a modified carbon fiber);

[0141] The basic model of the adjuvant is related to the mass of the mixed powder and the volume of the highly ductile composite;

[0142] The basic model of the adjuvant includes a second objective function and a second constraint;

[0143] Among them, the second objective function is the mass of mixed powder and the volume of high ductility composite material;

[0144] The second constraint is:

[0145] The bulking agent is 2%-4% of the mixed powder mass;

[0146] The water reducing agent is 0.5%-2% of the mixed powder mass;

[0147] The modified carbon fiber is 1%-3% of the total volume of the high ductility composite material.

[0148] Example 2

[0149] A method for determining a formula of a high-ductility composite material based on lake sediments, using the determination system in Example 1 to perform the following steps:

[0150] (1) Use the acquisition module to obtain lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , particle distribution characteristics of cement and ultrafine sand in lakes and reservoirs;

[0151] (2) According to the principle of closest packing, with the goal of maximizing the amount of ultrafine sand, the first determination module is used to determine the optimal formula of the mixed powder;

[0152] (3) Determine the optimized formula of high ductility composite materials using the second determination module and the basic model of auxiliary agents.

[0153] Example 3 (Spray repair of high ductility composite material)

[0154] A method for preparing a high-toughness composite material based on lake sediments comprises the following steps:

[0155] S1: Obtain the sediment from the Three Gorges Reservoir area, mix the sediment, red mud and steel slag in a mass ratio of 6:2:2, place the mixture in an oven, dry it at 80°C, remove excess water, and ensure that the material is evenly dried; put the dried mixture into a high-temperature furnace, set the temperature to 300°C, control the calcination time to 2 hours, and then cool it naturally; add 1.0 mol / L sodium hydroxide to the cooled mixture, the mass ratio (mixture: sodium hydroxide) = (10:1), mix it thoroughly, heat it again to 150°C, keep it for 1 hour, and then cool the alkali-heat-modified material to room temperature, and grind it to a specific surface area of ​​not less than 500m 2 / kg of lake sludge-red mud-steel slag modified mixture;

[0156] S2: Testing lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO 2 , particle distribution characteristics of ordinary Portland cement and ultrafine sand from lakes and reservoirs;

[0157] S3: According to the principle of the most dense packing of powders, with the goal of maximizing the amount of ultrafine sand, for the spray repair casting method, the control index of the characteristic value of the powder of the lake reservoir ultrafine sand for spray repair of high ductility composite materials is set. See Table 1 for details.

[0158] According to the indicators, the content of lake sludge-red mud-steel slag modified mixture is 10%, blast furnace ore powder is 25%, nano-SiO 2 10% of silicate cement and 55% of ordinary silicate cement. The above raw materials are collectively referred to as cementitious materials. The mass ratio of cementitious materials to ultra-fine sand from lakes and reservoirs is 55:45.

[0159] S4: The preparation and modification method of waste carbon fiber includes: screening and cleaning the carbon fiber composite material of the discarded aircraft shell, cutting, crushing and grinding to obtain short fiber-like carbon fiber and resin powder with a length of 20 mm; soaking the short fiber-like carbon fiber in a NaOH solution with a concentration of 1.0 mol / L, stirring for 30 minutes, taking out and drying in an oven at 105°C to obtain recycled carbon fiber.

[0160] S5: weigh a calcium-magnesium composite expansion agent according to 2% of the mass of the mixed powder material, weigh a high-performance water reducer and an appropriate amount of water according to 1.5% of the mass of the mixed powder material, dissolve the high-performance water reducer in water (wherein the mass ratio of the water reducer to water is 1:1) for later use, and weigh 2% of the total volume of the high-ductility composite material to obtain the waste modified carbon fiber.

[0161] S6: According to the ultra-fine sand of lakes and reservoirs, ordinary Portland cement, nano-SiO 2 , lake sludge-red mud-steel slag modified mixture, blast furnace ore powder are added to the mixer in sequence, stirred for 60 seconds, then calcium magnesium composite expansion agent and waste carbon fiber are added, the mixer is stirred for 30 seconds, and then water reducing agent is added and stirred for 60 seconds, and then sprayed, with a spraying pressure of 1MPa. A high ductility composite material can be obtained for spraying construction.

[0162] S7: Compressive strength and flexural strength tests were carried out in accordance with the relevant provisions of JC / T 2381-2016 "Repair Mortar". The specimens were cured under standard conditions. The flexural strength test was carried out on the 40mm×40mm×160mm prism specimens, and the compressive strength test was carried out on the cubes with a side length of 40mm. The test results are as follows Figure 3 and Figure 4 shown.

[0163] Example 4 (High-ductility composite material for hydraulic pumping)

[0164] The difference from Example 3 is that

[0165] S3, for the hydraulic pumping casting method, set the control index of the characteristic value of the ultra-fine sand from lakes and reservoirs for hydraulic pumping high-ductility composite material powder, see Table 2 for details;

[0166] According to the indicators, the content of lake sludge-red mud-steel slag modified mixture is 15%, blast furnace ore powder is 28%, and nano-SiO 2 7%, ordinary Portland cement 50%, the above raw materials are collectively called cementitious materials. The mass ratio of cementitious materials to ultra-fine sand in lakes and reservoirs is 40:60;

[0167] S5, weighing a calcium-magnesium composite expansion agent according to 1.5% of the mass of the mixed powder material, weighing a high-performance water reducer and an appropriate amount of water according to 2% of the mass of the mixed powder material, dissolving the high-performance water reducer in water (wherein the mass ratio of the water reducer to water is 1:1) for later use, and weighing waste modified carbon fibers according to 2% of the total volume of the high-ductility composite material;

[0168] S6, no spraying step is performed.

[0169] Other steps and conditions are the same as in Example 3.

[0170] The compressive strength of the hydraulic pumping high-ductility composite material prepared by this embodiment is 37.2 MPa (3d), 72.6 MPa (7d), and 94.5 MPa (28d); the flexural strength is 9.1 MPa (3d), 11.8 MPa (7d), and 13.2 MPa (28d). The test standards and conditions are the same as those in Example 3.

[0171] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A system for determining the formula of high-ductility composite materials based on lake sediments, characterized in that: include: Acquisition module, to obtain the particle distribution characteristics of lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO2, cement and lake ultrafine sand; The first determination module takes the maximum amount of lake ultrafine sand as the target, and is used to determine the formula optimization model of the mixed powder according to the particle distribution characteristics of the lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO2, cement and lake ultrafine sand; The mixed powder formula optimization model includes a first objective function and a first constraint condition; The second determination module is used to determine the formula of the high-ductility composite material according to the formula optimization model of the mixed powder and the basic model of the auxiliary agent.

2. A system for determining a formula of a high-ductility composite material based on lake sediments according to claim 1, characterized in that: The particle distribution characteristics include characteristic particle size and cumulative particle size distribution percentage; Among them, the corresponding cumulative particle size distribution percentage is determined by the characteristic particle size of the modified mixture of lake sludge-red mud-steel slag, blast furnace ore powder, nano-SiO2, cement and lake ultrafine sand.

3. The system for determining the formula of high-ductility composite materials based on lake sediments according to claim 1, characterized in that: When the maximum particle size of the ultrafine sand in the lake does not exceed 150 μm, the composite material obtained according to the formula determined by the determination system is used as a high-ductility composite material for spray repair. The first objective function is: D8-12 (0.68 μm), D46-54 (15.25 μm) and D89-91 (102.46 μm); in, The first constraint condition is: 40%≤x 超细粉沙 ≤60% wt ; In the above formula, i is any one of the modified mixture of lake sludge-red mud-steel slag, blast furnace ore powder, nano-SiO2, cement and lake ultrafine sand; x is the mass percentage of any raw material in the mixed powder; D is the particle size of each raw material in the mixed powder.

4. The system for determining the formula of a high-ductility composite material based on lake sediments according to claim 1, characterized in that: When the maximum particle size of the ultrafine sand in the lake does not exceed 300 μm, the composite material obtained according to the formula determined by the determination system is a high-ductility composite material for hydraulic pumping. The first objective function is D8-12 (0.84 μm), D46-54 (26.57 μm) and D89-91 (201.15 μm); in, The first constraint condition is: 40%≤x 超细粉沙 ≤60%wt; In the above formula, i is any one of the modified mixture of lake sludge-red mud-steel slag, blast furnace ore powder, nano-SiO2, cement and lake ultrafine sand; x is the mass percentage of any raw material in the mixed powder; D is the particle size of each raw material in the mixed powder.

5. The high-ductility composite material based on lake sediments according to claim 1, characterized in that: The auxiliary agent includes one or more of a water reducing agent, an expansion agent and a modified carbon fiber.

6. A system for determining a formula of a high-ductility composite material based on lake sediments according to claim 5, characterized in that: The basic model of the adjuvant includes a second objective function and a second constraint; Wherein, the second objective function is the mass of the mixed powder and the volume of the high ductility composite material; The second constraint is: The amount of expansion agent added is 2%-4% of the mass of the mixed powder; and / or The amount of water reducing agent added is 0.5%-2% of the mass of the mixed powder; and / or The added amount of the modified carbon fiber is 1%-3% of the total volume of the high-ductility composite material.

7. A method for determining a formula of a high-ductility composite material based on lake sediments, characterized in that: The determination system according to any one of claims 1 to 6 is used to perform the following steps: (1) Use the acquisition module to obtain the particle distribution characteristics of lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO2, cement and lake ultrafine sand; (2) According to the principle of closest packing, with the goal of maximizing the amount of ultrafine sand, the first determination module is used to determine the optimal formula of the mixed powder; (3) Determine the formula of the high ductility composite material using the second determination module and the basic model of the auxiliary agent.

8. A high-ductility composite material based on lake sediments, characterized in that: Including the following ingredients: Lake sludge-red mud-steel slag modified mixture, blast furnace ore powder, nano-SiO2, cement, lake ultra-fine sand and auxiliary agents; The amount of each raw material used complies with the formula of the high-ductility composite material determined by the determination system described in any one of claims 1 to 6 or the determination method described in claim 7.

9. The high-ductility composite material based on lake sediments according to claim 8, characterized in that: The lake sludge-red mud-steel slag modified mixture is prepared by uniformly mixing lake sludge, red mud and steel slag in a mass ratio of (4-6):(1-2):(1-2), followed by high-temperature calcination and alkali-heat modification.

10. A method for preparing a high-ductility composite material based on lake sediments, characterized in that: The following steps are involved: The raw material ratio of the high-ductility composite material is obtained according to the determination system according to any one of claims 1 to 6 or the determination method according to claim 7; Weigh each raw material according to the raw material ratio for later use; Ultrafine sand from lakes and reservoirs, cement, nano-SiO2, a modified mixture of lake and reservoir sludge-red mud-steel slag, and blast furnace ore powder are sequentially added into a mixer and stirred evenly to obtain a mixture; Adding auxiliary agents to the mixture and stirring the mixture evenly, the high-ductility composite material is obtained.

Citation Information

Patent Citations

  • Mix proportion design method of high-toughness cement-based engineering composite material based on uniform experiments and ACE nonparametric regression

    CN107330144A

  • High-strength and high-ductility cement-based composite material and preparation method thereof, and application of nano-cellulose in composite material

    CN115991589A

  • High-ductility cement-based composite material capable of being poured underwater and preparation method thereof

    CN117865614A

  • High-ductility concrete and preparation method thereof

    CN118063171A